Clinical outcomes and early- prognostic biomarkers of primary biliary cholangitis with ductopenia - Wang, Wenjuan; Zhang, Guo; Liu, Hui; Lv, Lingna; Chang, Jing; Liu, Zefeng; Ye, Huilan; Ding, Huiguo; Han, Ying (Frontiers in Immunology, 2025)
BackgroundDuctopenia drives biochemical failure and histological progression in primary biliary cholangitis (PBC), influencing its course and prognosis, but its prevalence, features, and prognosis remain unclear. This study aimed to characterize ductopenia in PBC and identify early predictive biomarkers.MethodsFrom August 2013 to April 2025, 518 of the biopsy-proven PBC patients were enrolled, analyzed for demographics, pathology, and clinical features, and grouped by ductopenia presence. 201 patients were followed until June 15, 2025, with liver-related adverse events (including TIPS, splenectomy with portosystemic shunt or portoazygous devascularization, liver failure, death, or liver transplantation) as endpoints. Kaplan-Meier and Cox regression assessed prognosis.ResultsThe overall proportion of patients with PBC and ductopenia was 56.76% (294/518), Notably, ductopenia was present in 24.83% (74/298) of patients with early-stage disease. Compared with the group without ductopenia, the ductopenia group showed significantly higher levels of cholestasis indicators (such as TBIL, ALP, GGT, and TBA) and autoantibodies (ANA, AMA anti-gp210), but significantly lower levels of liver synthetic function indicators (such as ALB and cholinesterase) and blood components (RBC, PLT, and HGB) (all P<0.05). The median follow-up time was 7.60 years (interquartile range: 5.80–9.20 years). The prevalence of liver-related adverse events was significantly higher in PBC patients with ductopenia than in those without (P<0.05). Cox regression analysis confirmed that ductopenia (HR=8.868, 95% CI: 1.135–69.307, P=0.037) was an independent risk factor for the occurrence of liver-related adverse events in patients with PBC. Multivariable logistic regression analysis identified that serum ANA(≥1:1000) (OR= 2.180, 95% CI: 1.261–3.769), elevated GGT (OR = 1.002, 95% CI: 1.001–1.003, P= 0.001) and TBIL (OR= 1.020, 95% CI: 1.005–1.035), lowed ALB (OR= 0.943, 95% CI: 0.896–0.993) as biomarkers for ductopenia in patients with early-stage PBC.ConclusionsDuctopenia is relatively common in patients with PBC, and its prevalence significantly increases with disease progression. Ductopenia was an independent risk factor for the occurrence of liver-related adverse events in patients with PBC. ANA(≥1:1000), TBIL, GGT, and ALB are early predictive biomarkers for ductopenia in patients with PBC.